2022
DOI: 10.1136/bmjopen-2020-048108
|View full text |Cite
|
Sign up to set email alerts
|

High haemoglobin levels and mortality in males with intracerebral haemorrhage: a retrospective cohort study

Abstract: ObjectivesTo examine the association between high haemoglobin levels and outcomes in intracerebral haemorrhage (ICH) in a multicentre cohort study.DesignProspective multicentre cohort study.Settings21 tertiary hospitals across mainland China.ParticipantsA total of 5318 consecutive in-hospital spontaneous ICH patients were recruited between January 2012 and June 2016.Primary and secondary outcome measuresHaemoglobin levels were measured on admission. Binary or ordinary logistic regression was used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A recent study ( 12 ) showed a U-shaped association between hemoglobin concentration and stroke sequelae and recurrence, with either too high or too low hemoglobin concentrations being associated with stroke disability, death and recurrence. Meanwhile, a multicentre study ( 14 ) noted that elevated hemoglobin concentrations within 3 months of onset were associated with poor prognosis in men but not significantly in women with cerebral hemorrhage. Several previous publications ( 15 17 ) suggest that dyslipidaemia is a known risk factor for cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study ( 12 ) showed a U-shaped association between hemoglobin concentration and stroke sequelae and recurrence, with either too high or too low hemoglobin concentrations being associated with stroke disability, death and recurrence. Meanwhile, a multicentre study ( 14 ) noted that elevated hemoglobin concentrations within 3 months of onset were associated with poor prognosis in men but not significantly in women with cerebral hemorrhage. Several previous publications ( 15 17 ) suggest that dyslipidaemia is a known risk factor for cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Tf level in response to iron deficiency may be the adoptive mechanism after anemic/hypoxic injury. Hemoglobin (Hb) is the iron‐containing oxygen‐transport metalloprotein in the red blood cells that is vital for oxygen supply in the brain (Zhang, Shu, Chen, et al, 2022), and higher Hb level was associated with increased mortality and disability in ischemic stroke patients (Zhang, Shu, Li, et al, 2022). However, in iron deficiency conditions, the suppression of Hb and red blood cell levels also leads to an anemic/hypoxic state, which induces hypoxia‐inducible factor‐1 (HIF‐1) expression (Rolfs et al, 1997).…”
Section: The Role Of Iron In Ischemic Strokementioning
confidence: 99%
“…96 Observational studies have mostly demonstrated an association between anemia and poor outcomes among ICH patients, though again not without inconsistency in the results (Table ). 66,[97][98][99][100][101][102][103][104] In a metaanalysis of 7 cohort studies from 2009 to 2016 that included 7328 ICH patients, anemia was associated with increased 30-day mortality (OR, 1.72; 95% CI, 1.37-2.15; P = .02; I 2 = 64%), and increased risk of poor functional outcome at 3 months (OR, 2.29; 95% CI, 1.16-4.51; I 2 = 91%; P < .0001). 105 This considerable heterogeneity should be noted when interpreting the data, as the definition of anemia and measurement of Hb varied significantly between studies.…”
Section: Intracerebral Hemorrhagementioning
confidence: 99%